Pengaruh komposisi perekat tanin urea formaldehida terhadap keteguhan rekat kayu lapis meranti - Adi Santoso; Paribotro Sutigno (Jurnal Penelitian Hasil Hutan, 1995)
Based on previous  research  tannin formaldehyde  resin from  Acacia   decurens     bark can  be used for  exterior plywood adhesive.  To reduce  the cost,   the effect of urea addition  to produce tannin   urea formaldeliyde   resin has been  studied.   The other treatment  employed is percentage of paraformaldehyde as hardener.The  results  show  that   the  properties  of  tannin  urea formaldehyde   resin  conform  with Indonesian standard for  phenol formaldehyde  resin.   The effect  of weight ratio based on mol ratio on  the plywood  bonding strenght is significant,  while the effect ofpercentage  of hardener   is not significant.    the  weight ratio tannin.urea =  1:2 with three percentages of hardener meet German standardfor exterior plywood (type AW-100).   The  weight ratio tannin urea =  1=2,5  with 2,5%   and 5% hardener  meet the standard, while the weight ratio tannin:urea  =  1:3  do not meet the standard. The plywood bonding strenght  tends    to  decrease if using more urea.  Based on economic consideration,  it is recommended 10   use weight  ratio tannin.urea  =   1:2,5  based on  mol  ratio with percentage of hardener 2,5%   of liquid resin.